CCD OBSERVATIONS OF THE POLAR AM HERCULIS - Shugarov, S. Yu.; Ostrova, N. I. (Одеські астрономічні публікації, 2017)
Results of two CCD runs of V observations of AM Her obtained on August 1 and 2, 1998 are reported. The moment of minimum brightness at HJD 2451027.4014 ± 0.d0012 is in a good agreement with an ephemeris by Andronov et al. (2001).